Bioinspired self-flowing wood chemical treatment - Xuan Wang; Sheldon Q. Shi (Nature Communications)
Abstract Wood has complex composition and structure, which make it difficult to achieve consistent and controllable treatment. A self-flowing process presented for the chemical treatment of wood is inspired by liquid transportation in trees during photosynthesis and tree growth, whereby liquid in the soil is brought through the natural vessels and/or fiber tracheids. In this process, wood lumbers are placed in a tank containing treatment chemicals such as preservatives, fire retardants, or reactive agents. Through an absorbent sheet bridging the untreated lumber to an overflow tank, the chemicals are drawn into the lumber under capillary force and pressure difference, so that continuous treatment occurs inside the wood. Effectiveness of the self-flowing process is evaluated and compared to conventional immersion and vacuum wood treatment methods. The self-flowing method is very effective for wood delignification, which is six and four times more effective than that from immersion and vacuum pressure treatment methods, respectively. The self-flowing process allows a more uniform wood treatment compared to that from the immersion and vacuum pressure methods. A mathematical model was developed to describe the self-flowing process. This model can accurately predict the treatment time required for achieving desired results under various conditions.